Democracy & digital governance : help or hindrance? - Amalina Anuar (2021)
The Biden administration sees democracy as the solution to digital authoritarianism at home and abroad. But doubling down on existing principles and exclusive clubs may not be the most effective answer to shared problems of digital and data governance.